2019
DOI: 10.1016/j.comptc.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Excited state dynamics initiated by an electromagnetic field within the Variational Multi-Configurational Gaussian (vMCG) method

Abstract: The Variational Multi-Configurational Gaussian (vMCG) approach offers a framework to perform exact trajectory-based quantum dynamics. Herein we use two model vibronic coupling Hamiltonians of pyrazine to explore, for the first time, the influence of the coupling between the external field and the Gaussian basis functions (GBFs) in vMCG on the dynamics. We show that when the excitation pulse is short compared to the nuclear dynamics, vertical projection without a field and explicit description of the external f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…The only notable difference is the damping of the fast 1 MLCT ↔ 3 MLCT oscillations for the 60 fs pulse. This is expected, 8,63 as the pulse duration approaches the period of the observed oscillations. These results also justify the utilization of impulsive excitation to the 1 MLCT states for the simulation of excited-state dynamics of [Fe(bmip) 2 ] 2+ .…”
Section: A Quantum Dynamicsmentioning
confidence: 56%
“…The only notable difference is the damping of the fast 1 MLCT ↔ 3 MLCT oscillations for the 60 fs pulse. This is expected, 8,63 as the pulse duration approaches the period of the observed oscillations. These results also justify the utilization of impulsive excitation to the 1 MLCT states for the simulation of excited-state dynamics of [Fe(bmip) 2 ] 2+ .…”
Section: A Quantum Dynamicsmentioning
confidence: 56%
“…This implementation is straightforward in the Qu-Eh method due to the use of a single time-dependent potential energy surface. Other alternative methods of including an external electric field in dynamics can be accomplished by including the product of the field with the transition dipole moment in the equation of motion, 26,27 propagator for semi-classical dynamics, 28 a local-control method, 29 and a Floquet Hamiltonian. 30 A more detailed review can be found in the paper of Antipov…”
Section: Please Cite This Articlementioning
confidence: 99%
“…Trajectory-based approaches to nonadiabatic dynamics are powerful tools for predicting the fate of a molecule after photo-excitation [1][2][3][4][5][6][7][8][9][10][11][12][13] or the products of a collision reaction [14][15][16][17] . The underlying approximations, in the treatment of nuclear dynamics 3,12,[18][19][20] and in the description of electron-nuclear coupling 12,[21][22][23][24][25] , make them computationally efficient, at least compared to a numerically-exact solution of the time-dependent Schr ödinger equation 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Trajectory-based approaches to nonadiabatic dynamics are powerful tools for predicting the fate of a molecule after photo-excitation [1][2][3][4][5][6][7][8][9][10][11][12][13] or the products of a collision reaction [14][15][16][17] . The underlying approximations, in the treatment of nuclear dynamics 3,12,[18][19][20] and in the description of electron-nuclear coupling 12,[21][22][23][24][25] , make them computationally efficient, at least compared to a numerically-exact solution of the time-dependent Schr ödinger equation 19 . Clearly, the computational efficiency comes at the price of losing accuracy or missing critical features, such as tunnelling and zero-point energy [26][27][28][29][30] , interferences 31,32 , quantum decoherence [33][34][35][36] , to name some of the usual suspects.…”
Section: Introductionmentioning
confidence: 99%